Catch rider - Lyne, Jennifer H. (Clarion Books, 2013)
Despite her poor background and ferocious competition from more privileged girls, fourteen-year-old Sid pursues her dream of becoming a catch rider--a show rider who can ride anything--with help from her Uncle Wayne.